2007
DOI: 10.1063/1.2757172
|View full text |Cite
|
Sign up to set email alerts
|

Sampling of states for estimating the folding funnel entropy and energy landscape of a model alpha-helical hairpin peptide

Abstract: Protein folding times are many orders of magnitude shorter than would occur if the peptide chain randomly sampled possible configurations, which implies that protein folding is a directed process. The detailed shape of protein's energy landscape determines the rate and reliability of folding to the native state, but the large number of structural degrees of freedom generates an energy landscape that is hard to visualize because of its high dimensionality. A commonly used picture is that of an energy funnel lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…On the other hand, apparently the nucleation-condensation process of at least some of the six previously and nine here investigated proteins also involves early funneling in the sense of multiple pathways as suggested by the funnel model (Wolynes et al, 1995(Wolynes et al, , 1996Onuchic et al, 1996;Shoemaker et al, 1997Shoemaker et al, , 1999Nymeyer et al 1998;Wolynes, 2001;Simler et al, 2006;Kameda & Takada, 2006;Chapagain et al, 2007;Kamiya et al, 2007;Kim et al, 2007;Lindberg & Oliveberg, 2007;MacCallum et al, 2007) and a decrease in molecular volume (see, e.g., Nölting et al, 1997;Kataoka et al, 1997;Pollack et al, 1999) as suggested by the hydrophobic collapse model (Rackovsky & Scheraga, 1977;Dill, 1985Dill, , 1990aDill, , 1990bDill et al, 1995;Akiyama et al, 2000;Hausrath, 2006;Arai et al, 2007).…”
Section: Nucleation-condensation Mechanism Of Foldingmentioning
confidence: 67%
See 1 more Smart Citation
“…On the other hand, apparently the nucleation-condensation process of at least some of the six previously and nine here investigated proteins also involves early funneling in the sense of multiple pathways as suggested by the funnel model (Wolynes et al, 1995(Wolynes et al, , 1996Onuchic et al, 1996;Shoemaker et al, 1997Shoemaker et al, , 1999Nymeyer et al 1998;Wolynes, 2001;Simler et al, 2006;Kameda & Takada, 2006;Chapagain et al, 2007;Kamiya et al, 2007;Kim et al, 2007;Lindberg & Oliveberg, 2007;MacCallum et al, 2007) and a decrease in molecular volume (see, e.g., Nölting et al, 1997;Kataoka et al, 1997;Pollack et al, 1999) as suggested by the hydrophobic collapse model (Rackovsky & Scheraga, 1977;Dill, 1985Dill, , 1990aDill, , 1990bDill et al, 1995;Akiyama et al, 2000;Hausrath, 2006;Arai et al, 2007).…”
Section: Nucleation-condensation Mechanism Of Foldingmentioning
confidence: 67%
“…The native elements of secondary structure are then thought to form in the collapsed state by structural rearrangement. Two further important models, the zipper model (Dill et al, 1993;Thompson et al, 1997) and funnel model (Wolynes et al, 1995(Wolynes et al, , 1996Onuchic et al, 1996;Shoemaker et al, 1997Shoemaker et al, , 1999Nymeyer et al 1998;Wolynes, 2001;Simler et al, 2006;Kameda & Takada, 2006;Chapagain et al, 2007;Kamiya et al, 2007;Kim et al, 2007;Lindberg & Oliveberg, 2007;MacCallum et al, 2007) emphasize zipper-like folding processes and parallel pathways of folding, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, fine-scale details such as sharp barriers (as above) or local roughness in the landscape [38,39] typically cannot be recovered. We note that the problem of resolving fine details in the landscapes of biomolecules is ubiquitous across different reconstruction approaches, whether due to Gaussian filtering by a probe as above, coarse binning [8], or inadequate sampling [40].…”
mentioning
confidence: 99%
“…This can be taken as an indication that the transition state possesses a restricted degree of freedom compared to both the relaxed and the quenched LHCII conformers. A relatively wide landscape of possible transition state conformers is typically discussed for protein folding, and computational investigation have been performed for small globular polypeptides (e.g., (48)(49)(50)). The negative value of DS q y points toward the existence of a defined intermediate in the transition between the unquenched and quenched form of the complex, rather than a pure transition state, which is unresolved due to temporal resolution of the measurement (see (32,38,50) for discussions relating to intermediate in protein folding).…”
Section: Thermodynamic Characterization Of the Transition Statementioning
confidence: 99%